Mission relationships, employment relationships, or alliance relationships: wetland management from the perspective of carbon trading - Wu, Shansong; Bai, Yuntao; Li, Jiahao; Yang, Yueling (Frontiers in Ecology and Evolution, 2025)
In recent years, wetland ecosystems have faced severe degradation, prompting governments to provide carbon compensations to enterprises engaged in wetland conservation efforts. The relationships between governments and enterprises in wetland management are primarily categorized into three models: mission relationships, employment relationships, and alliance relationships. Determining the optimal application scope for each model remains a critical challenge. To address this, this paper constructs three differential game models and conducts a comparative analysis of their equilibrium outcomes. The findings reveal distinct optimal scenarios for governments and enterprises. For governments, the employment relationships model maximizes social benefit when the per-unit benefit of wetland management is small; the mission relationships model is optimal for moderate benefits, and the alliance relationships model for large benefits. For enterprises, the employment relationships model maximizes social benefit when the per-unit benefit is small; the alliance relationships model is optimal for moderate benefits, and the mission relationships model for large benefits.